ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, MEDIA PROMOSI, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Toko Bangunan Ben Berkah Kota Semarang Barat ) - Mamila Hidayatullah, 14.05.51.0020; Maskur, Ali (Students Journal of Economic and Management, 2018)
This study aims to test and analyze the effect of product, price perception, promotion and location to the purchase decision. Analyzer used multiple regression, as for to test hypothesis using t test. Data collection through questionnaires with measurements using Likert scale 5 (five) alternative answers. The object of the research is the consumers of Ben Bless Shop West Semarang. The number of samples in this study is 100 respondents. The sampling technique uses that Purposive sampling. The result of the research shows that (1) The productquality has a significant effect on purchasing decision, (2) Price perception have significant effect to purchasing decision, (3) Promotion media has no significant effect on purchasing decision and (4) Location has significant effect to purchasing decision.Keywords: product quality, price perception, promotion media , location, purchase decision